(untitled) (Libyan Journal of Ecological & Environmental Sciences and Technology, 2022)
In 1st August 2021, during the sunset time in Shmaikh village 30 Km. south to Bani-Walid city (N 31°26,482 E 13°57,461), a sub-adult Rüppell’s vulture Gyps rueppelli was found in the front yard of a house. This is the first record of G. rueppelli in Libya. Despite, the distribution range of this species is in the Sahel region and East Africa. Previously, there are only three vulture’s species recoded in Libya; Egyptian Vulture Neophron percnopterus, Griffon Vulture Gyps fulvus and Lappet-faced Vulture Torgos tracheliotos. According to the IUCN-Red list, the Rüppell’s vulture has mentioned as a critically endangered category D.